2017
DOI: 10.1089/lap.2016.0467
|View full text |Cite
|
Sign up to set email alerts
|

Single-Port Laparoscopic Surgery Can Be Performed Safely and Appropriately for Colon Cancer: Short-Term Results of a Pilot Randomized Controlled Trial

Abstract: SPLS for colon cancer is feasible and can be performed by following oncologic principles. However, surgeons should be aware of the potential for unexpected adjacent organ injury ( ClinicalTrial.gov identifier: NCT01203969).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…Four of the studies 12,13,31,32 reported this outcome. The SILS CME had smaller total wound length (WMD = −3.02 [−3.25 to −2.80]; P < .00001) with considerable heterogeneity I 2 = 82% (Figure 4).…”
Section: Wound Length (In Centimeters)mentioning
confidence: 87%
See 2 more Smart Citations
“…Four of the studies 12,13,31,32 reported this outcome. The SILS CME had smaller total wound length (WMD = −3.02 [−3.25 to −2.80]; P < .00001) with considerable heterogeneity I 2 = 82% (Figure 4).…”
Section: Wound Length (In Centimeters)mentioning
confidence: 87%
“…None of the studies employed an enhanced recovery protocol. Two studies 12,31 provide a description of their discharge criteria, and 3 of the studies 12,30,31 reported on their readmission data. The 2 studies that report on long-term outcomes include a percentage of stage III patients who received adjuvant chemotherapy that ranged between 20% and 21.5% in the SILS CME group.…”
Section: Selection and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the laparoscopic colorectal resections also offer similar long-term oncologic and survival outcomes as compared to open surgery (5,9,(13)(14)(15)(16). The clinical benefits of laparoscopic surgery seem to be due to the small incision in the abdominal wall, reduced bowel manipulation and thereby reduced surgical trauma (17).…”
Section: Original Articlementioning
confidence: 99%
“…A total of 194 studies were identified from Scopus and Medline and other electronic databases. Among them, 5 RCTs (n=525), published between 2012 and 2018, were eligible for inclusion (17,22,37,53,54); and the reasons for ineligibility are described in PRISMA flow chart Figure 1. The salient characteristics of included trials are described in Table 1.…”
Section: Characteristics Of Selected Trialsmentioning
confidence: 99%